Geo-ontoepistemologias decoloniais: Educação Linguística e "Português como Língua Acolhimento" - Francisco Leandro Oliveira Queiroz (2022)
Abstract In the last few years, the decoloniality (MIGNOLO, 2017a, 2015, 2008, 2003; WALSH, 2017, 2016, 2013; QUIJANO, 2014; CASTRO-GÓMEZ and GROSFOGUEL, 2007) has becoming an option each time more necessary to bring the body back and mark the unmarked (MENEZES DE SOUZA, 2019, 2018) in the language and in the knowledge production, mainly in the contexts of the Global South, like the brazilian case. Bringing the body back and marking the unmarked carry premises that refuse the universal as a category capable of professing the only history and the natural as a possible strategy to justify the social hierarchies, with their radical inequality (SANTOS, 2019). The universal and the natural reveal the necessity of rethinking the knowledge from its own geopolitics and body-politics, addressing the social issue as a consequence of modernity (MIGNOLO, 2010a, 2000) and from coloniality (MIGNOLO, 2017b, 2010a). In the Educational Linguistics site, the decolonial perspective is fundamentally relevant for reporting the coloniality of language (VERONELLI, 2021), digging spaces for other redesigns, without ignoring the constant tension and without dispensing objections from time to time. In those terms, the goal of this thesis is to problematize the Portuguese as a Host Language from my teacher-educator locus of enunciation of Portuguese and from the decolonial geo-ontoepistemologies. The methodology is conversational and interpretative-reflexive, considering the literary choice, their views, experiences and social expectations among the political, ethical and educational contemporary demands. The main results point to a strong coloniality of language, crossing the being, the feeling and the acting of the affected subjects by the modern oppression, reflecting directly on the being and knowing domination, in a way that intersubjectivities and knowledges obey colonial patterns of power. The results also point to the necessity to identify-interrogate-interrupt this own coloniality, calling attention to the reconstruction of the Portuguese as a Host Language from decolonial premises, assuming the teacher and the student as co-authors of this process locally. Keywords: Decolonial geo-ontoepistemologies. Educational Linguistics. Portuguese as a Host Language.